Изоантигены и изоантитела человека в норме и патологии - Косяков Павел Николаевич (Медицина, 1974)
Экземпляры: КХ (20201028) / Инвентарный номер: 601093 / Сис.шифр: 616.9 / Авт.знак: К 72 / ГРНТИ: 76 / ББК: 5